2011
DOI: 10.1590/s1517-83822011000200015
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of tomato seedlings with Trichoderma Harzianum and Arbuscular Mycorrhizal Fungi and their effect on growth and control of wilt in tomato seedlings

Abstract: A green house study was conducted to investigate the ability of an isolate of Trichoderma harzianum (P52) and arbuscular mycorrhizal fungi (AMF) in enhancing growth and control of a wilt pathogen caused by Fusarium oxysporum f. sp. lycopersici in tomato seedlings. The plants were grown in plastic pots filled with sterilized soils. There were four treatments applied as follows; P52, AMF, AMF + P52 and a control. A completely randomized design was used and growth measurements and disease assessment taken after 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 4 publications
2
19
0
5
Order By: Relevance
“…This association increases the supply of mineral nutrients to the plant, particularly those whose ionic forms have a poor mobility rate or those which are present in low concentration in the soil and thus promote plant growth (Ercolin & Reinhardt 2011). AM fungi also have the potential in plant disease control that has been demonstrated by various workers (Akhtar & Siddiqui 2008a;Kobra et al 2009;Singh et al 2010;Mwangi et al 2011). Several mechanisms are involved in disease control by AM fungi such as sink competition with infection sites, morphological changes in roots and root tissues, and changes in chemical constituents in plant tissue (Linderman 2000).…”
mentioning
confidence: 95%
“…This association increases the supply of mineral nutrients to the plant, particularly those whose ionic forms have a poor mobility rate or those which are present in low concentration in the soil and thus promote plant growth (Ercolin & Reinhardt 2011). AM fungi also have the potential in plant disease control that has been demonstrated by various workers (Akhtar & Siddiqui 2008a;Kobra et al 2009;Singh et al 2010;Mwangi et al 2011). Several mechanisms are involved in disease control by AM fungi such as sink competition with infection sites, morphological changes in roots and root tissues, and changes in chemical constituents in plant tissue (Linderman 2000).…”
mentioning
confidence: 95%
“…For Trichoderma spp., isolated conditioning showed the best performance, followed by seed coating, being still superior to untreated seeds. Likewise, Mwangi et al (2011) emphasize that T. harzianum can be used to increase the growth of tomato seedlings. When evaluating seedling growth, it was observed that the suspension of B. subtilis bacterial cells provided lower results compared to the other techniques.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of mycorrhizal root colonization in the treatment AMF and treatment with both AMF and T. harzianum showed that they were not significantly different (Mwangi, et al (2011)), also they demonstrated that T. harzianum showed compatibility with AMF and no inhibitory effects on the development of mycorrhizal colonization was observed, also Sr'amek, et al 2000 found that T. harzianum did not affect colonization by AMF in three balcony plants (Verbena, Torenia, Diascia) inoculated with both AMF and T. harzianum. Data presented as the means of three replicates ± SD.…”
Section: Effect Of Treatments On Wilt Pathogen Controlmentioning
confidence: 91%